The Shadow of Spirit in William Gibson's Matrix Trilogy. - Olsen, L. (Extrapolation (Kent State University Press))
Examines the matrix trilogy (comprised of `Neuromancer (1984), `Count Zero' (1986), and `Mona Lisa Overdrive' (1988)) by William Gibson), all of which give the sense of irresolution in the cyberpunk response to the spiritual. Gibson's exhibition of a kind of fashionable condescension toward religion; His complex and contradictory portrayal of the spiritual; Definition of cyberpunk; The quasi-mind/body dualism; Details of each book.